2018
DOI: 10.1002/cpp.2174
|View full text |Cite
|
Sign up to set email alerts
|

A case series of Acceptance and Commitment Therapy (ACT) for reducing symptom interference in functional neurological disorders

Abstract: There is limited high-quality evidence supporting psychological treatments for functional neurological disorders (FNDs), and what evidence exists suggests that the impact of such treatments could be improved. One way to increase effectiveness is to utilize approaches that can have impact across heterogeneous FND presentations. Acceptance and Commitment Therapy (ACT) targets a transdiagnostic process called psychological flexibility and is used effectively to integrate multidisciplinary treatments in other clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…We identified 19 relevant studies, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] the characteristics and full author list of which are outlined in table 1. Elsewhere these studies are referred to by the first author's surname followed by the year of publication.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 19 relevant studies, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] the characteristics and full author list of which are outlined in table 1. Elsewhere these studies are referred to by the first author's surname followed by the year of publication.…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this this version posted February 21, 2023. ; https://doi.org/10.1101/2023.02. 20.23286183 doi: medRxiv preprint…”
Section: Data Managementmentioning
confidence: 99%
“…[17] There is evidence that ACT effectively reduces distress and disability in chronic pain [18] and long-term medical conditions [19] while it has also been recommended for the treatment of functional neurological disorders generally. [13, 20] ACT can be delivered in one-to-one or group formats. It is feasible and acceptable to deliver to patients with psychosis in a brief group format [21] and can be effectively delivered online through guided and unguided modules of learning.…”
Section: Introductionmentioning
confidence: 99%
“…Limited research to date has looked at the possible application of ACT to epilepsy and FNEA in adults although recent research suggests that ACT-informed treatments are effective in addressing recurrent and impairing functional somatic syndromes (FSS) in adolescents (Kozlowska et al, 2018). The extant literature has mainly focused on the use of ACT in treating epilepsy in adults (Lundgren et al, 2008) although small case studies and case series (Graham, O’Hara & Kemp, 2017; Graham, Stuart, et al, 2017) have indicated that ACT shows promise in the management of functional neurological disorders but again this research is solely focused on adult populations.…”
Section: Introductionmentioning
confidence: 99%